Phenotype and function of peripheral blood γδ T cells in HIV infection with tuberculosis - Zou, Shi; Xiang, Yanni; Guo, Wei; Zhu, Qi; Wu, Songjie; Tan, Yuting; Yan, Yajun; Shen, Ling; Feng, Yong; Liang, Ke (Frontiers in Cellular and Infection Microbiology, 2022)
Background Although γδ T cells play an essential role in immunity against Human Immunodeficiency Virus (HIV) or Mycobacterium tuberculosis (MTB), they are poorly described in HIV infection with tuberculosis (TB). Methods The phenotypic and functional properties of peripheral blood γδ T cells in patients with HIV/TB co-infection were analyzed compared to healthy controls and patients with HIV mono-infection or TB by direct intracellular cytokine staining (ICS). Results The percentage of Vδ1 subset in HIV/TB group was significantly higher than that in TB group, while the decreased frequency of the Vδ2 and Vγ2Vδ2 subsets were observed in HIV/TB group than in TB group. The percentage of CD4+CD8- Vδ2 subset in HIV/TB group was markedly lower than in TB group. However, the percentage of CD4+CD8+ Vδ2 subset in HIV/TB group was markedly higher than HIV group or TB group. A lower percentage TNF-α and a higher percentage of IL-17A of Vδ2 subset were observed in HIV/TB group than that in HIV mono-infection. The percentage of perforin-producing Vδ2 subset was significantly lower in HIV/TB group than that in HIV group and TB group. Conclusions Our data suggested that HIV/TB co-infection altered the balance of γδ T cell subsets. The influence of HIV/TB co-infection on the function of γδ T cells to produce cytokines was complicated, which will shed light on further investigations on the mechanisms of the immune response against HIV and/or MTB infection.